Digital image analysis supports a nuclear‐to‐cytoplasmic ratio cutoff value below 0.7 for positive for high‐grade urothelial carcinoma and suspicious for high‐grade urothelial carcinoma in urine cytology specimens. Issue 2 (5th November 2018) - McIntire, Patrick J.; Snow, Justin T.; Elsoukkary, Sarah S.; Soong, Lauren; Sweeney, Jacob; Robinson, Brian D.; Siddiqui, Momin T.
Abstract: Background: Urinary cytology is sensitive and specific for diagnosing and screening high‐grade urothelial carcinomas (HGUC). The Paris System (TPS) for urinary cytology was introduced in 2016 to standardize reporting. According to TPS diagnostic categories of HGUC and suspicious for HGUC (SHGUC), the average nuclear‐to‐cytoplasm (N:C) ratio of atypical cells should be ≥0.7. The objective of the current study was to measure the N:C ratio of urine cytology specimens with HGUC and SHGUC diagnoses and biopsy‐proven HGUC follow‐up. Methods: A cohort of 64 cases (HGUC, 49 cases; SHGUC, 15 cases) from 57 patients was constructed. Urine cytology slides were scanned into whole‐slide digital images. The nuclear and cytoplasmic areas were enumerated by digital image analysis (DIA), and the N:C ratios were measured. Results: In total, 640 cells were analyzed by DIA (HGUC, 490 cells; SHGUC, 150 cells). For HGUC and SHGUC, the average N:C ratios were 0.57 and 0.53, respectively. The maximum average N:C ratio was 0.73 for HGUC and 0.68 for SHGUC. HGUC had higher average N:C ratio ( P < .001), higher average nuclear area ( P < .001), higher average maximum N:C ratio ( P = .005), and higher average maximum nuclear area ( P = .006) compared with SHGUC. Conclusions: The N:C ratios for the HGUC (0.57) and SHGUC (0.53) categories are lower than those previously suggested in TPS. The authors advocate reducing the N:C ratio below the current threshold of 0.7. Abstract : Digital image analysis demonstrates that the average nuclear‐to‐cytoplasmic ratio of malignant urothelial cells in urine specimens with diagnoses of high‐grade urothelial carcinoma (HGUC) and suspicious for HGUC (SHGUC) is below the 0.7 threshold set by The Paris System. The authors advocate for reducing the nuclear‐to‐cytoplasmic ratio for the HGUC and SHGUC categories in The Paris System.